2015
DOI: 10.1002/jemt.22485
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic role of curcumin in oxidative DNA damage caused by formaldehyde

Abstract: In conclusion, the oxidative stress caused by formaldehyde exposure was reduced with the application of curcumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Curcumin also reduced the nociceptive response in both phases I and II. Ciftci et al demonstrated that Curcumin could reduce the level of MDA and significantly increase the TAC, reducing the oxidative DNA damage in cells [ 55 ]. The level of oxidative stress is partially reduced due to its scavenging potential.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin also reduced the nociceptive response in both phases I and II. Ciftci et al demonstrated that Curcumin could reduce the level of MDA and significantly increase the TAC, reducing the oxidative DNA damage in cells [ 55 ]. The level of oxidative stress is partially reduced due to its scavenging potential.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has shown that curcumin can efficiently protect cells from H 2 O 2 -induced oxidative cell injury [ 38 , 48 ]. Due to its antioxidant potential, curcumin was shown to have the ability to reduce lipid peroxidation and DNA damage, while increasing the level of vitamin C, vitamin E, and total anti-oxidant capacity [ 49 , 50 ]. Furthermore, curcumin has been shown to induce phase II metabolism while suppressing phase I metabolizing enzymes such as renal ornithine decarboxylase [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also consistent with previous reports. For instance, curcumin has been reported to provide protection against the effect of a number of different oxidative molecules (21,23,24). in the formaldehyde group as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…In our group, significantly increased renal MDA levels were found in the formaldehyde group, suggesting that formaldehyde may cause tissue damage through oxidative stress. Also, previous reports showed that formaldehyde may oxidize other structural and vital molecules such as certain other proteins and nucleic acids, in addition to lipids(20)(21)(22).…”
mentioning
confidence: 99%